Unleashing the Potentials of Housing Sector in Nigeria as Perceived by Users (International Journal of Built Environment and Sustainability, 2017)
Housing is a basic need and a human right. The role that housing plays in the social and economic development of a country cannot be underestimated.  Interventions in housing by government are widely acknowledged as one of the ways by which the social aspect of the life of the citizenry can be impacted especially through mass housing otherwise called social housing. This paper aims to examine the various potentials in the housing sector in order to enhance the delivery of more housing to Nigerians. A survey research approach was used in the study. Descriptive analysis was employed to explain the potentials in the housing sector. Housing deficit in Nigeria currently stands at about 17 million units. Efforts to meet and rectify the deficit will need a concerted effort of individuals and government. It requires unleashing the potentials in the housing sector to stimulate growth in the economy, thereby diversifying the economy from the mono to a multi sector economy.  Interventions of governments at all levels as well as the involvement of informal sector in the housing sector will have a multiplier effect. It will generate multiple employment opportunities which will in turn stimulate the economy through the circulation of money in the system. The paper noted that interventions in housing sector will stimulate industries in the production of local building materials. Additionally, ailing companies will be revitalized, thereby improving the standard of living of the citizens. The paper concludes that strengthening and repositioning of agencies such as the Federal Mortgage Bank of Nigeria, Real Estate Developers Association of Nigeria, Nigeria Mortgage Refinance Company, will accelerate the release of the potentials in the housing sector and thereby enhance the delivery of affordable houses for Nigerians.